Periodontal Defects in the A116T Knock-in Murine Model of Odontohypophosphatasia. (May 2015) - Foster, B.L.; Sheen, C.R.; Hatch, N.E.; Liu, J.; Cory, E.; Narisawa, S.; Kiffer-Moreira, T.; Sah, R.L.; Whyte, M.P.; Somerman, M.J.; Millán, J.L.
Mutations in ALPL result in hypophosphatasia (HPP), a disease causing defective skeletal mineralization. ALPL encodes tissue nonspecific alkaline phosphatase (ALP), an enzyme that promotes mineralization by reducing inorganic pyrophosphate, a mineralization inhibitor. In addition to skeletal defects, HPP causes dental defects, and a mild clinical form of HPP, odontohypophosphatasia, features only a dental phenotype. The Alpl knockout ( Alpl -/- ) mouse phenocopies severe infantile HPP, including profound skeletal and dental defects. However, the severity of disease in Alpl -/- mice prevents analysis at advanced ages, including studies to target rescue of dental tissues. We aimed to generate a knock-in mouse model of odontohypophosphatasia with a primarily dental phenotype, based on a mutation (c.346G>A) identified in a human kindred with autosomal dominant odontohypophosphatasia. Biochemical, skeletal, and dental analyses were performed on the resulting Alpl +/A116T mice to validate this model. Alpl +/A116T mice featured 50% reduction in plasma ALP activity compared with wild-type controls. No differences in litter size, survival, or body weight were observed in Alpl +/A116T versus wild-type mice. The postcranial skeleton of Alpl +/A116T mice was normal by radiography, with no differences in femur length, cortical/trabecular structure or mineral density, or mechanical properties. Parietal bone trabecular compartment was mildly altered. Alpl +/A116T mice featured alterations in the alveolar bone, including radiolucencies and resorptive lesions, osteoid accumulation on the alveolar bone crest, and significant differences in several bone properties measured by micro–computed tomography. Nonsignificant changes in acellular cementum did not appear to affect periodontal attachment or function, although circulating ALP activity was correlated significantly with incisor cementum thickness. The Alpl +/A116T mouse is the first model of odontohypophosphatasia, providing insights on dentoalveolar development and function under reduced ALP, bringing attention to direct effects of HPP on alveolar bone, and offering a new model for testing potential dental-targeted therapies in future studies.